Bifunctional Platinum‐Incorporated Polyoxoniobate Derived Catalyst for N‐formylation of Piperidine Using CO2. Issue 2 (13th October 2022) - Chudatemiya, Vorakit; Kikkawa, Soichi; Hirayama, Jun; Takahata, Ryo; Teranishi, Toshiharu; Tamura, Masazumi; Yamazoe, Seiji
Abstract: Alkaline salt of platinum‐incorporated heteropolyoxoniobate [Pt(Nb6 O19 )2 ] 12− (Pt(Nb6)2 ) was fabricated and applied for N ‐formylation of various amines including piperidine under CO2 and H2 atmosphere. Pt(Nb6)2 achieved the selective formation of 1‐formylpiperidine, whereas the absence of Pt species, H2, and CO2 resulted in a trace amount of the product. The structural characterization revealed that the sandwich‐type structure of Pt(Nb6)2 was transformed into Pt nanoparticles incorporated with polyoxoniobates ([Nb6 O19 ] 8− ) on the NbOx bulk matrix (NbPOM‐PtNPs/NbOx ) under reaction conditions. The N ‐formylation of amines in the presence of CO2 and H2 proceeded by the bifunctional NbPOM‐PtNPs/NbOx where the basic sites of [Nb6 O19 ] 8− and the redox property of Pt promoted the generation of formamides. Abstract : The catalytic properties of alkaline salts of sandwich‐type [Pt(Nb6 O19 )2 ] 12− ((Pt(Nb6)2 ) were elucidated by N ‐formylation of amines under CO2 and H2, which resulted in highly selective formamides. After reactions, a formation of Pt nanoparticles and incorporated with [Nb6 O19 ] 8− clusters on NbOx support (NbPOM‐PtNPs/NbOx ) occurred, which acted as the bifunctional catalyst for N ‐formylation of amines using CO2 as a carbonyl source.